REFORMULASI PENGATURAN HAK CIPTA KARYA BUATAN ARTIFICIAL INTELLIGENCE MELALUI DOKTRIN WORK MADE FOR HIRE - Syifa' Silvana (Fakultas Hukum Universitas Udayana, 2023)
The purpose of this study is to examine the potential for reformulating copyright regulations regarding works produced by Artificial Intelligence (AI) through the application of the "work made for hire" doctrine in the Copyright Law in Indonesia. The writing method used is normative juridical using 3 (three) types of approaches, namely: statutory approach, conceptual approach, and comparative approach. The results of this study show that the reformulation of copyright regulations in Indonesia, taking into account the "work made for hire" doctrine, has great potential to overcome the legal complexities related to AI works. This reformulation could ensure fair copyright protection while providing incentives for the development of artificial intelligence technologies. This study also provides references from international legal practices that can serve as a guide in formulating copyright regulations that are appropriate to the development of AI technology in Indonesia. With careful implementation, this reformulation can provide a strong legal basis for protecting copyright of AI works and encouraging innovation in the digital era.